ONLINE COURSE RECOMMENDATION SYSTEMS - Baltabekov, Y.S.; Moldagaliev, B.K. (Journal of Emerging Technologies and Computing, 2024)
Today in our world exists many online courses, so today it is hard to students to choose the courses they like. This paper work is about recommendation system based on user`s interests in his profile, this technique called Content Based, and on similarity with other users, this technique called Collaborative filtering, and hybrid method. My aim is to make such system, which will recommend courses that will be interesting to users. By using these techniques it can be improved efficiency of the recommendation system and make the life of the users more easier. Because in the process of study, the user will not be difficult to receive information and he will not be border.